2007
DOI: 10.1038/ni1505
|View full text |Cite
|
Sign up to set email alerts
|

Minimal activation of memory CD8+ T cell by tissue-derived dendritic cells favors the stimulation of naive CD8+ T cells

Abstract: Of the many dendritic cell (DC) subsets, DCs expressing the monomorphic coreceptor CD8 alpha-chain (CD8alpha) are localized permanently in lymphoid organs, whereas 'tissue-derived DCs' remain in nonlymphoid tissues until they 'capture' antigen and then move to local lymph nodes. Here we show that after lung infection, both naive and memory CD8+ 'killer' T cells responded to influenza virus antigens presented by lymph node-resident CD8alpha+ DCs, but only naive cells responded to antigens presented by lung-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
133
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 43 publications
10
133
2
Order By: Relevance
“…Legge demonstrated that these CD11b 1 inflammatory DC indeed boost CD8 1 effector activity in the lung [49]. Other studies have shown that CD103 1 CD11b À lung cDC cannot present antigen to virus-specific effector CD8 1 T lymphocytes [47]. Secondly, CD11b 1 DC can display direct antiviral potential through the release of TNF and production of iNOS-derived NO, as shown during Listera monocytogenes infection [50], and thus might also contribute to influenza pathogenesis and systemic disease.…”
Section: Lung DC Subsets and Antiviral Immunity: Influenza As The Parmentioning
confidence: 94%
See 1 more Smart Citation
“…Legge demonstrated that these CD11b 1 inflammatory DC indeed boost CD8 1 effector activity in the lung [49]. Other studies have shown that CD103 1 CD11b À lung cDC cannot present antigen to virus-specific effector CD8 1 T lymphocytes [47]. Secondly, CD11b 1 DC can display direct antiviral potential through the release of TNF and production of iNOS-derived NO, as shown during Listera monocytogenes infection [50], and thus might also contribute to influenza pathogenesis and systemic disease.…”
Section: Lung DC Subsets and Antiviral Immunity: Influenza As The Parmentioning
confidence: 94%
“…The CD11b À migratory DC stimulated CD4 1 and CD8 1 lymphocyte responses, whereas CD11b 1 DC were very poorly immunogenic. A population of CD8a 1 CD11b À non-migratory cDC also acquired antigen from migratory CD11b À and CD11b 1 cells and crosspresented viral antigen to CD8 1 T cells [2,47]. Depletion of lung CD11b À cDC in langerin-diphtheria toxin receptor Tg mice (langerin-DTR) and of resident CD8a 1 cDC using CD11c-DTR Tg mice severely hampered the induction of virus-specific tetramer-positive CD8 1 T cells and delayed viral clearance from the lung [2].…”
Section: Lung DC Subsets and Antiviral Immunity: Influenza As The Parmentioning
confidence: 99%
“…18,[34][35][36] In vitro programming was accomplished in the following manner. In all experiments, day 7 pmel T EM cells were frozen.…”
Section: In Vitro Programming and Adoptive Cell Transfermentioning
confidence: 99%
“…Within the draining LN, DC subsets, primarily CD103 + DCs that migrated from the infected respiratory tract, as well as LN resident CD8α + DCs, present antigen to CD8 T cells (14)(15)(16)(17)(18). These DCs can acquire IAV antigens by at least three distinct mechanisms: (i) through direct infection, (ii) through phagocytosis of necrotic or apoptotic IAV-infected epithelial cells, or (iii) through membrane exchange with infected cells and transfer of peptide-loaded MHC I (1)(2)(3)(4)(5)(6)(19)(20)(21)(22).…”
mentioning
confidence: 99%